GEOLOGY AND DEPOSITIONAL ENVIRONMENT OF CAMPANO-MAASTRICHTIAN SEDIMENTS IN THE ANAMBRA BASIN, SOUTHEASTERN NIGERIA: EVIDENCE FROM FIELD RELATIONSHIP AND SEDIMENTOLOGICAL STUDY - O.C, Adeigbe; A. E, Salufu (Earth Sciences Research Journal, 2009)
The study area lies within the Anambra Basin and it is made up of Enugu Shale, Mamu Formation, Ajali Sandstone, and Nsukka Formation. This study aimed at determining the geology and depositional environmental of these formations through field relationship and grain size distribution morphologic studies.The field data shows Enugu Shale as fissile, light grey with extraformational clast which graded into Mamu Formation whichis made up of shale, coal and sandy shale. It passes upward into Ajali Sandstone which is characterized by cross beds, Herringbonestructures and Ophiomorpha burrows. The youngest formation within the basin is Nsukka Formation.The granulometric study of Mamu Formation shows fine to medium grains, coarse, medium to fine grain for Mamu and Ajali Formation respectively. The standard deviation indicates poorly sorted. The kurtosis shows leptokurtic, platykurtic to very leptokurtic for both while the skewness values indicate positive and symmetrical in all except for Ajali Sandstone that is negatively skewed.The bivariate and the multivariate results reveal shallow marine and fluvial deposits for both Mamu Formation and Ajali Sandstone respectively. The paleocurrent direction of Ajali Sandstone indicates southwest while the provenance is northeast.The fissility of Enugu Shale suggests that it was deposited in low energy environment, distal to proximal lagoon environment.The presence of extraformatonal clast within Enugu Shale indicates fluvial incursion. However, the textural analysis of Mamu Formation suggests a sediment deposited in a low energy environment which favoured deposition of fine to medium size sediments that is, estuary environment. Textural result of Ajali Sandstone in the study area coupled with the field data such as Herring-bone structures, and Ophiomorpha burrows, revealed that Ajali Sandstone was deposited in a tidal environment probably littoral environment. While the light grey colour observed in the Nsukka Formation suggests sediments deposited under an oxidizing marine environment.